2021
DOI: 10.1111/ijfs.15388
|View full text |Cite
|
Sign up to set email alerts
|

The effect of annealing on resistant starch content of different crop types: a systematic review and meta‐analysis study

Abstract: Summary The growing demand for functional foods with a high resistant starch content (per cent RS) could be met by annealing starch modification. Through a meta‐analysis, this study sought to shed light on the effect of annealing on the resistant starch content of various crop types. Twenty‐one studies published between 2000 and 2020 were selected and eighty data points were extracted to be analysed using meta‐essential tools. Hedge’s d Standardised Mean Difference (SMD) was designated for the effect size appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Faridah et al . (2021) have reported the effect of annealing parameters such as incubation time, temperature and water ration as well as amylose content on the changes of RS due to annealing. The objective of this study was to investigate the effect of annealing on relative crystallinity degree related to RS content based on the type of starch allomorphs using a literature review and meta‐analysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faridah et al . (2021) have reported the effect of annealing parameters such as incubation time, temperature and water ration as well as amylose content on the changes of RS due to annealing. The objective of this study was to investigate the effect of annealing on relative crystallinity degree related to RS content based on the type of starch allomorphs using a literature review and meta‐analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Starch crystallinity is one of the factors affecting RS content during annealing (Ashwar et al, 2016) among other factors such as plant genetics, amylopectin chain distribution and interactions with starch protein and lipid. Faridah et al (2021) have reported the effect of annealing parameters such as incubation time, temperature and water ration as well as amylose content on the changes of RS due to annealing. The objective of this study was to investigate the effect of annealing on relative crystallinity degree related to RS content based on the type of starch allomorphs using a literature review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta‐analysis is a technique to summarise and combines results from multiple studies with a quantitative approach. This method has been chosen because it generates more accurate results than the individual study and analyses the significant parameters (Faridah et al ., 2021a, 2021b). The goals of the meta‐analysis are to obtain new results, synthesise of contradictory results, increase analytical precision, better representation and help in planning and generating new results (Lovatto et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have evaluated the effect of unit operations on modifying properties in foods such as starches (Faridah et al ., 2021a, 2021b), mycotoxin control (Mousavi Khaneghah et al ., 2018; Emadi et al ., 2021), sensory acceptance (Grigor et al ., 2016) and microbiological control in fruit juices (Silva et al ., 2015) through meta‐analysis. To mediate such contrasting results, the aim of this review paper was to assess the impact of ultrasound process parameters on the interfacial properties of proteins by analysing the results of surface hydrophobicity by a meta‐analysis approach.…”
Section: Introductionmentioning
confidence: 99%